Challenges of Online Learning Faced by IIUM Malay Undergraduates during COVID-19: A Case Study - Nur Atiera Binti Yunus; Iyad M. Y. Eid (IIUM Journal of Religion and Civilisational Studies, 2024)
This study examined the challenges of online learning faced by Malay undergraduate students studying at the International Islamic University Malaysia (IIUM) during the global pandemic of COVID-19. The study used a qualitative research technique and face-to-face semi-structured interviews for collecting data. The interview includes details about the participants' demographics, backgrounds, and the key study-related questions. Furthermore, the research employed open-ended questions to prompt participants to openly discuss their experiences without being restricted by predetermined responses. Participants were provided with information sheets and email consent forms before the interview session. Ten IIUM undergraduates were chosen using the purposive sample approach. Six females and four males participated in the research, and they were Malay students from Malaysia. The data was transcribed word for word into a Microsoft Word document and then classified into themes, analysed, interpreted, and validated. The results of the study showed that the students faced challenges in terms of internet connection, technological devices, social interaction, learning environment, and physical and mental health. The paper highlights the challenges of online learning encountered by Malay undergraduates studying at IIUM during COVID-19 pandemic. The new learning method was implemented in unprecedented global circumstances. Students remained at home, which became an alternative learning environment. Meanwhile, they went through some negative situations affecting the learning process. This paper presents and discusses five challenges and supports the findings by citing previous studies. The research results provide concerned agencies, like the Malaysian Ministry of Education, with a sociological understanding of the challenges involved in e-learning. They identify to what extent the available infrastructure for information and communication needs expansions and improvements to overcome internet access limitations in rural and urban areas. Furthermore, the research offers insight into the necessary initiatives that the Ministry of Higher Education in Malaysia should undertake to help in reducing the challenges facing higher education students.